Specificity of RNA Binding by CPEB: Requirement for RNA Recognition Motifs and a Novel Zinc Finger - Hake, Laura E. (American Society for Microbiology, 1998)
CPEB is an RNA binding protein that interacts with the maturation-type cytoplasmic polyadenylation element (CPE) (consensus UUUUUAU) to promote polyadenylation and translational activation of maternal mRNAs in Xenopus laevis. CPEB, which is conserved from mammals to invertebrates, is composed of three regions: an amino-terminal portion with no obvious functional motif, two RNA recognition motifs (RRMs), and a cysteine-histidine region that is reminiscent of a zinc finger. In this study, we investigated the physical properties of CPEB required for RNA binding. CPEB can interact with RNA as a monomer, and phosphorylation, which modifies the protein during oocyte maturation, has little effect on RNA binding. Deletion mutations of CPEB have been overexpressed in Escherichia coli and used in a series of RNA gel shift experiments. Although a full-length and a truncated CPEB that lacks 139 amino-terminal amino acids bind CPE-containing RNA avidly, proteins that have had either RRM deleted bind RNA much less efficiently. CPEB that has had the cysteine-histidine region deleted has no detectable capacity to bind RNA. Single alanine substitutions of specific cysteine or histidine residues within this region also abolish RNA binding, pointing to the importance of this highly conserved domain of the protein. Chelation of metal ions by 1,10-phenanthroline inhibits the ability of CPEB to bind RNA; however, RNA binding is restored if the reaction is supplemented with zinc. CPEB also binds other metals such as cobalt and cadmium, but these destroy RNA binding. These data indicate that the RRMs and a zinc finger region of CPEB are essential for RNA binding.